إمامة المتغلب في الفقه الإسلامي: دراسة مقارنة - Mohamed (حسام الدين خليل فرج), Hossam El-Din Khalil F (At-Tajdid - Intellectual Refereed Journal, 2018)
Abstract The paper explores the issue of the imamate al-Mutaghallib (leader who assumed power via coups d'état) and explains that is had not been given a fair share of investigation albeit its importance due to its influence on the political stability and insinuation to support anti-establishment. It will present the different directions in the Islamic jurisprudence and their proofs along with the historical context that accommodate this issue. This is very pertinent to the different context that it has become in our time after the emergence of nation States. Subsequently, a deliberation of the differing views based on the different situations of al-taghallub (overcome) and the means to preserve the Maqāsid Shariʽah in its imamate. Keywords: Imamate, Rulers, Imamate of a Military Coup, nation state, maqāsid Sharīʽah.